The weight of water: values, civic engagement, and collaborative groundwater management on the U.S. high plains - Lauer, Stephen (Kansas State University, 2020)
Rural communities in the U.S. High Plains rely on groundwater from the declining Ogallala aquifer. I apply the sociological concepts of social structure, culture, and agency to understand the relationships between farmers/producers and groundwater management. My mixed methods approach includes quantitative modeling of secondary data, a survey of producers across the Ogallala Aquifer region, interviews with producers in Western Kansas, and a case study of sustained civic engagement among the producers who formed the Wichita County Water Conservation Area (WCA). My model of secondary data shows no association between groundwater extraction and human development at the county level. This suggests that the benefits of groundwater extraction are not being reinvested into local human and financial capitals. My interviews with producers provide support for a treadmill of production and for reinvestment into local cultural and social capitals. Consistent with a treadmill of production, producers described how investments in irrigation infrastructure make it costly for them to conserve groundwater. They described how irrigation increases cultural and social capital through higher populations, increased community cohesion, and maintaining their way of life. My survey of producers indicates that an overwhelming majority (92%) agree that groundwater should be conserved, primarily to benefit future generations (86%), support local jobs and businesses (66%), provide insurance against drought (63%), and continue the economic viability of irrigated agriculture (60%). Most producers (72%) believe they are already doing all they can individually to conserve groundwater on their operations. Interviews with producers indicate that those who become involved voluntary group conservation efforts find additional ways to conserve. Most producers (84%) are open to the possibility that voluntary group conservation may be effective and that they might have something personally to contribute to such efforts, but few (7%) are currently involved. My interviews show that values, beliefs, and norms are important to their individual and collective groundwater management decisions. However, my model of survey data suggests that differences in producers’ values, beliefs, and norms do not explain which producers are civically engaged in voluntary group conservation efforts. I argue that civic engagement is contingent, in that structural and cultural factors must align in a particular community to enable producers to choose to pursue voluntary group conservation. My interviews with producers and case study of the Wichita County WCA support this explanation. Wichita County was primed for voluntary group conservation through structural and cultural factors, including a quantity of groundwater that made conservation efforts both urgent and promising, a single town that producers value and which economically relies on groundwater, and previous efforts that raised local awareness about groundwater conservation. The Wichita County WCA team sustained civic engagement through solidarity, developing a shared sense of meaning and purpose, and taking a diffuse and relational approach to leadership. They managed emotions such as fear, grief, despair, and frustration in a manner consistent with the Public Narrative model of social action. Key factors in their success included an early focus on teambuilding, diverse stakeholder representation, bringing in an outside facilitator, frequent and respectful community outreach, and partnering with state and local government. Voluntary group efforts are effective at conserving groundwater and merit support.
Keywords: Ogallala Aquifer; Groundwater Conservation; Sustained Civic Engagement; Rural Sociology; Natural Resource Management; Community Development